2012
DOI: 10.1371/journal.pone.0048094
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the Maxwell 16 System for Extraction of Influenza Virus RNA from Diverse Samples

Abstract: This study evaluated the performance of the Maxwell 16 System (Promega) for extraction of influenza virus (flu-v) RNA from diverse samples compared to a classical manual method (QIAamp Kit, QIAGEN). Following extraction by the two methods, all samples were analyzed by Real-time RT-PCR. Results revealed that the use of the standard Maxwell 16 protocol (Maxwell 16-S) resulted in good linearity and precision across a wide concentration range and higher sensitivity of detection from flu-v stock suspensions than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
4
2
0
Order By: Relevance
“…The mean Ct values of the baseline samples were 29.6 and 30.1, respectively, for the Maxwell 16 System and QIAamp extraction methods, and the respective standard deviation (SD) was 0.5 and 0.6, which was in accordance with our previous study [10]. It was considered to be a significant change in RNA yield when a mean Ct value goes beyond the possible variation range (more or less than 1.96 SD) of the assay method by comparison with the corresponding baseline value.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The mean Ct values of the baseline samples were 29.6 and 30.1, respectively, for the Maxwell 16 System and QIAamp extraction methods, and the respective standard deviation (SD) was 0.5 and 0.6, which was in accordance with our previous study [10]. It was considered to be a significant change in RNA yield when a mean Ct value goes beyond the possible variation range (more or less than 1.96 SD) of the assay method by comparison with the corresponding baseline value.…”
Section: Resultssupporting
confidence: 90%
“…The samples treated with buffer B were extracted with the QIAamp Kit and eluted in 60 μl Buffer AVE (Qiagen). Although having different starting and elution volumes (200-μl input and 50-μl output vs 140-μl input and 60-μl output), the two extraction methods in conjunction with either of the two RT-PCR assays below exhibited close detection limits (∼10 -0.3 TCID 50 /ml of the virus) according to our previous study [10] and the preliminary experiments in this study [Liu H,…”
Section: • • Virus Preparationsupporting
confidence: 53%
“…During this study, Isohelix swabs were selected over Copan swabs due to easier handling and higher sensitivity for sample collection, and this approach has been successfully used by other studies (12). Furthermore, our results demonstrated that automated RNA extraction was as efficient (13,14) as manual kits for extracting SARS-CoV-2, which has been previously noted using phenol-chloroform (15).…”
Section: Discussionsupporting
confidence: 53%
“…For example, in the anthrax mailing attack of 2001 in the US, Bacillus anthracis was cultured from the victim's cerebral spinal fluid and blood, and subsequently genotyped to identify the source of the microorganism (Keim, Budowle, & Ravel, 2011). Chemical‐, mechanical‐, or heat‐based DNA extraction methods are generally effective for bacteria and viruses (Alessandrini et al, 2019; Brauge et al, 2018; Cho et al, 2014; Hennechart‐Collette, Niveau, Martin‐Latil, Fraisse, & Perelle, 2019; Liu et al, 2012; Thomas et al, 2013), with the exception of bacteria endospores.…”
Section: Dna Extraction From Human Remains and Non‐conventional Samplesmentioning
confidence: 99%